Periodic solutions of linear impulsive differential inclusions - Skripnik, N. V. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We establish sufficient conditions for the existence of periodic R-solutions of linear differential inclusions with impulses at fixed times.